Numerical Simulations and Model Tests of the Mooring Characteristic of A Tension Leg Platform Under Random Waves - 谷家扬 杨建民 吕海宁 (China ocean engineering, 2013)
Analyzing the dynamic response and calculating the tendon tension of the mooring system are necessary for the structural design of a tension leg platform （TLP）. The six-degree-of-freedom dynamic coupling responses and the mooring characteristics of TLP under random waves are studied by using a self-developed program. Results are verified by the 1：40 scaling factor model test conducted in the State Key Laboratory of Ocean Engineering at Shanghai JiaoTong University. The mean, range, and standard deviation of the numerical simulation and model test are compared. The influences of different sea states and wave approach angles on the dynamic response and tendon tension of the mooring system are investigated. The acceleration in the center and corner of the deck is forecasted.